Health Care Provider Burnout in Syria During COVID-19 Pandemic's Omicron Wave - Hidar Alibrahim; Sarya Swed; Haidara Bohsas; Hiba Haj Saleh; Safwan Al-Rassas; Noor Hussain; Ayush Kumar; Bisher Sawaf (University Library System, University of Pittsburgh, 2023)
Background: Healthcare workers have dealt with a range of psychological problems during the COVID 19 epidemic, including sadness, mental discomfort, anxiety, and poor sleep. Burnout is a state of prolonged work stress-related psychological, emotional, and physical stress brought on by emotional weariness, depersonalization, and decreasing professional success. The goal of this study was to find out how many healthcare workers burned out during the Omicron wave of the COVID-19 pandemic and to find out what factors put them at risk for this psychological effect.   Methods: This cross-sectional research was performed in Syria during the current Omicron wave of COVID-19 pandemic to evaluate the Burnout experienced by Syrian physicians who treat COVID-19 patients. The inclusion criteria were all Syrian healthcare workers who treated COVID-19 patients the current Omicron wave of COVID-19. The data was collected between April 3 and March 20, 2022. We investigated whether the questionnaire used was valid and understandable to the participants.   Results: A total of (729) healthcare providers inquired in our study; however, 30 participants were disqualified because their answers were not fully completed. The overall age of the participants was 31±9, and the ratio of males to females was almost equal. The majority (47.5%) of the sample study's participants are residents, and 72.8% of the participants carried for COVID19 patients. The prevalence of high level of burnout among the sample study was 41.6%. Compared to men (22.3%), women were much more likely (27.9%) to report experiencing a high degree of emotional exhaustion, also the participants who carried for COVID19 patients were much more likely (30.1%%) to report experiencing a high degree of emotional exhaustion compared to others, which individuals who carried for COVID19 patients were 1.76 times more likely than participants who did not carry for COVID19 patients to experience severe burnout (OR:1.766, 95%CI:1.2-2.4, P-value<0.001).   Conclusion: Our research found severe burnout among Syrian health care providers during the omicron wave of COVID19, with clinicians carrying COVID19 patients being considerably more likely to express high burnout than others. For this reason, it is imperative that we collaborate with international humanitarian organizations to provide a suitable psychiatric environment for Syrian physicians and provide practical recommendations to address this important concern.